The effect of salinity on spotting features of Salmo trutta abanticus, S. trutta fario and S. trutta labrax of cultured brown trout - Kocabaş, M.; Başçinar, N. (2013)
Salmo trutta is one of the most important fish species due to its aquaculture potential, economic value and wide consumer demand and skin color is an important commercial trait in fish farming, given that this phenotype influences consumer acceptance, thereby determining the commercial value that fish can reach (Colihueque, 2010). Morphological differentiation can be due to two causes, genetic differences or environmental factors, or interaction between them. Environmental factors can produce phenotypic plasticity, which produce different phenotypes for the capacity of a genotype in different environmental conditions (Stearns, 1989; Scheiner, 1993). Salinity is one of the most relevant environmental parameters that effective in aquaculture (Brett, 1979). Several studies have been performed relation with phenotypic traits of salmonid species (Thymallus thymallus, Salmo salar m. sebago, Salmo trutta m. lacustris and Salvenilus alpines, Pakkasmaa et al., 1998; Salmo trutta, Oadri, 1959; İslam et al., 1973; Blanc et al., 1982, 1994; Skaala and Jørstad, 1988; Mezzera et al., 1997; Dyness et al., 1999; Pakkasmaa and Piironen, 2001; Agapova et al., 2002; Alexander and Adams, 2004; Aparicio et al., 2005; Keeley et al., 2005; Keeley et al., 2006; Bronte and Moore, 2007; Bud et al., 2009) although the knowledge is lack of information in the literature related to effect of salinity on spotting of brown trout. Published